From Gemeinschaft to Gesellschaft: Cracks in the Practical Values of Pancasila in the Semi-Urban Society - St. Hasmawati H; Heri Tahir; Ririn Nurfaathirany Heri; Bakhtiar Bakhtiar (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to analyze the shift in the practical values of Pancasila, particularly the Third and Fourth Principles, in the developing urban community in Pattallassang District, Takalar Regency. The study used a qualitative approach with a descriptive analytical type. Data were obtained through in-depth interviews, passive participant observation, and documentation of community leaders, government officials, local residents, and academics selected using purposive sampling. Data analysis adopted the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and conclusion drawing. While data validity was tested using triangulation of sources, techniques, and time. The results show that urbanization, economic pressures, and digital penetration have triggered the deconstruction of social solidarity in society. Gotong royong has shifted from a routine activity based on collective awareness to a conditional and transactional action. The practice of deliberation has also been distorted due to the dominance of efficiency rationality, elite capture, and the shift in communication to virtual spaces that weaken social closeness. In addition, the penetration of digital capitalism has given rise to an individualistic, consumptive, and hedonistic lifestyle. This research emphasizes the need for revitalization of public spaces and fostering Pancasila ideology based on digital-civic engagement that is more inclusive and contextual in developing peri-urban communities.